The Rise of World History Studies in Twentieth-Century China - Xu, Luo (History compass, 2010)
The essay is a brief survey of the rise of world history studies in China. It traces the origin of the political and academic interest in the world outside of China back to the mid-nineteenth century, and discusses the growth and changes in the institution, curriculum, and ideology in China’s world history field in the twentieth century and the early years of the twenty-first century. The emphasis of the essay is on the development of world history studies during the six decades of the People’s Republic of China after 1949, first under Soviet influence, and then under Western influence. It also addresses Chinese historians’ persistent effort to search for their own identity and build a Chinese system of world history studies.